Interfacial rheology and direct imaging reveal domain-templated network formation in phospholipid monolayers penetrated by fibrinogen. Issue 44 (25th October 2019) - Williams, Ian; Zasadzinski, Joseph A.; Squires, Todd M.
Abstract : The shear response of a phospholipid monolayer penetrated by fibrinogen is determined by the formation of a domain-templated protein network. Abstract : Phospholipids are found throughout the natural world, including the lung surfactant (LS) layer that reduces pulmonary surface tension and enables breathing. Fibrinogen, a protein involved in the blood clotting process, is implicated in LS inactivation and the progression of disorders such as acute respiratory distress syndrome. However, the interaction between fibrinogen and LS at the air–water interface is poorly understood. Through a combined microrheological, confocal and epifluorescence microscopy approach we quantify the interfacial shear response and directly image the morphological evolution when a model LS monolayer is penetrated by fibrinogen. When injected into the subphase beneath a monolayer of the phospholipid dipalmitoylphosphatidylcholine (DPPC, the majority component of LS), fibrinogen preferentially penetrates disordered liquid expanded (LE) regions and accumulates on the boundaries between LE DPPC and liquid condensed (LC) DPPC domains. Thus, fibrinogen is line active. Aggregates grow from the LC domain boundaries, ultimately forming a percolating network. This network stiffens the interface compared to pure DPPC and imparts the penetrated monolayer with a viscoelastic character reminiscent of a weak gel. When the DPPC monolayer is initially compressed beyond LE–LC coexistence, stiffening is significantly more modest and the penetrated monolayer retains a viscous-dominated, DPPC-like character.